2004
DOI: 10.1038/sj.npp.1300477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lorazepam on the Neuromagnetic Mismatch Negativity (MMNm) and Auditory Evoked Field Component N100m

Abstract: The mismatch negativity (MMN) as an auditory evoked potential is thought to reflect an early, preconscious attention process. While this component has gained great importance in studies on clinical populations and in basic research on auditory information processing, the involvement of different neurotransmitters in the generation of this component is less well understood. We investigated the impact of the benzodiazepine lorazepam as a GABA agonist on the neuromagnetic MMN (MMNm) and auditory evoked field comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…The important role of the GABA system in modulating MMN responses was showed by Smolnik et al (1998), who reported an increase in MMN amplitudes after the administration of benzodiazepine flumazenil. Rosburg et al (2004) also confirmed a relation between GABA and MMN by showing an increase in MMN latency under the effect of lorazepam. As the reduction in MMNm amplitude after scopolamine administration suggests, the cholinergic system could modulate MMN as well (Pekkonen et al 2001(Pekkonen et al , 2005.…”
Section: Introductionsupporting
confidence: 79%
“…The important role of the GABA system in modulating MMN responses was showed by Smolnik et al (1998), who reported an increase in MMN amplitudes after the administration of benzodiazepine flumazenil. Rosburg et al (2004) also confirmed a relation between GABA and MMN by showing an increase in MMN latency under the effect of lorazepam. As the reduction in MMNm amplitude after scopolamine administration suggests, the cholinergic system could modulate MMN as well (Pekkonen et al 2001(Pekkonen et al , 2005.…”
Section: Introductionsupporting
confidence: 79%
“…While there is strong support for the role of NMDA receptors in modulating MMN, the studies investigating the role of other neurochemical systems, including the dopaminergic (Kähkönen et al 2001Pekkonen et al 2002), serotonergic Umbricht et al 2002Umbricht et al , 2003Kähkönen et al 2005), cholinergic (Inami et al 2005;Baldeweg et al 2006;Knott et al 2006a, b), GABAergic (Nakagome et al 1998;Smolnik et al 1998;Rosburg et al 2004) and histaminergic (Serra et al 1996) systems have demonstrated inconsistent findings. Thus, the effects of other neurotransmitter systems on MMN generation warrant further investigation.…”
Section: Introductionmentioning
confidence: 95%
“…Intracranial data were compared with simultaneously recorded data from the scalp. Finally, all data were screened for a possible occurrence of long-term habituation, as previous studies have shown a response decrease of the MMN within experiments (McGee et al, 2001;Rosburg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%